Regeneration of the retina by stem cell transplantation therapy - Singh, M (2013)
One strategy to restore vision in retinitis pigmentosa and related retinal degenerations is by cell replacement. Typically, patients lose vision when the outer retinal photoreceptor layer is lost, and so the therapeutic ideal would be to restore vision at this stage of disease. It is not currently known if a degenerate retina lacking the outer nuclear layer of photoreceptor cells would allow the survival, maturation and reconnection of replacement photoreceptors, as prior studies used hosts with a pre-existing outer nuclear layer at the time of treatment. Here, using a murine model of severe human retinitis pigmentosa at a stage when no host rod cells remain, transplanted rod precursors are shown to reform an anatomically distinct and appropriately polarised outer nuclear layer. A trilaminar nuclear organisation is returned to the rd1 hosts that had only two retinal layers before treatment. The newly introduced rod precursor cells were able to resume their developmental programme in the degenerate host niche to become mature rods with light- sensitive outer segments, and reconnected with host neurons downstream. Visual function, assayed in the same animals before and after transplantation, was restored in animals with zero rod function at baseline. These observations suggest that a cell therapy approach may reconstitute a light-sensitive cell layer de novo and hence repair a structurally damaged visual circuit. Rather than placing discrete photoreceptors amongst pre-existing host outer retinal cells, total photoreceptor layer reconstruction may provide a clinically relevant model to investigate cell-based strategies for retinal repair.